2023
DOI: 10.1007/s10597-022-01073-y
|View full text |Cite
|
Sign up to set email alerts
|

How do Mental Health Services Foster Hope? Experience of People Accessing Services

Abstract: Hope is essential to mental health recovery, yet little is known about how mental health services can foster hope. This paper addresses the question: How can mental health services influence the sense of hope experienced by people who access their services? Sixty-one people who accessed a new mental health service were interviewed about their experiences, including about how the service had influenced their sense of hope. Interviews were analysed using constant comparative analysis. The data revealed that hope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The experience of receiving empathy (and/or a lack of) and reassurance from clinicians was regarded by most participants as significantly influencing their experience. This is in line with recent studies that found that empathic care from clinicians improved outcomes during therapy [42]. NBCS recommend all MDT members are trained to recognise and respond appropriately to psychological distress [21].…”
Section: Discussionsupporting
confidence: 84%
“…The experience of receiving empathy (and/or a lack of) and reassurance from clinicians was regarded by most participants as significantly influencing their experience. This is in line with recent studies that found that empathic care from clinicians improved outcomes during therapy [42]. NBCS recommend all MDT members are trained to recognise and respond appropriately to psychological distress [21].…”
Section: Discussionsupporting
confidence: 84%
“…In this context, based on theoretical and empirical data, several authors have focused on the enhancement of hope (e.g., Feldman & Dreher, 2012;Honey et al, 2023;Lopez et al, 2004;Pouyanfard et al, 2020;Safaralizadeh et al, 2022).…”
Section: Hope and Mental Healthmentioning
confidence: 99%
“…In this context, based on theoretical and empirical data, several authors have focused on the enhancement of hope (e.g., Cheavens et al, 2006;Feldman and Dreher, 2012;Honey et al, 2023;Lopez et al, 2004;Pouyanfard et al, 2020;Safaralizadeh et al, 2022) [33,34,[52][53][54][55].…”
Section: Hope and Mental Healthmentioning
confidence: 99%